Subgingival air-polishing treatment in patients with aggressive periodontitis - Trtić, Nataša; Bošnjak, Andrija P.; Arbutina, Radmila; Nikolić, Tatjana; Marin, Saša; Veselinović, Valentina; Kojić, Željka; Adamović, Tijana; Dolić, Olivera (Vojnosanitetski pregled, 2021)
Background/Aim. Periodontal tissue maintenance therapy is an important phase of the overall periodontal disease therapy. This paper aims to determine subgingival air-polishing efficacy with glycine powder in putative paropathogens reduction, plaque index, gingival bleeding index and probing depth. Methods. The study included 44 patients with aggressive periodontitis of both sexes, aged between 21 and 50, divided into two groups. Subgingival air-polishing was applied in the first group and sonic scaling in the control (second) group. Biofilm samples were taken from 5 deepest periodontal pockets before the therapy and 3 and 15 months after it. Paropathogens Aggreggatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsithya, Prevotella intermedia, Treponema denticola were detected by PCR analysis. Results. Paropathogens values were decreased after applied treatments. There was a statistically significant reduction in the mean value of full-mouth plaque (FMPS), from 43.00 to 14.90 (first group) and from 44.71 to 15.54 (second group), full-mouth bleeding score (FMBS) from 42.55 to 13.85 (first group) and from 43.04 to 15.17 (second group), as well as in probing depth from 3.40 to 2.64 (first group) and from 3.85 to 2.91 (second group), three months after the therapy. Conclusion. Subgingival air-polishing successfully reduces putative paropathogens and clinical parameters three months after the treatment.
Keywords: periodontal diseases; periodontal pocket; glycine; therapeutics; bacteria; polymerase chain reaction